Revisiting Ranganathan: The Making of Rule N° 5 - Alpin, A.M.; Belantara, Amanda (KULA, 2025)
Rule N°5: The Library Is a Growing Organism is a collaboratively created installation located in NYU’s main library that centers the voices of library workers in six sculptures. The work takes its name from Ranganathan’s five laws or “rules” of library science published in 1931 and focuses on how the spirit of the fifth rule or law, which reads “the library is a growing organism,” continues to inform the life and work of the library. As an interactive audio experience, Rule N°5 invites listeners to open doors and drawers, plug in, and push buttons to explore what it means to collect the world’s knowledge, preserve the past, and shape the future. Rule N°5 examines practices and objects that shape how we can search, who we will find, and what we remember.In this article, the makers behind the installation share stories of the project’s creation and a deeper inspection of the invisible labor and conversations about questions of power, authority, and the politics of seemingly innocuous library work that inform the work.